2013
DOI: 10.1075/avt.30.13van
|View full text |Cite
|
Sign up to set email alerts
|

Information structural transfer in advanced Dutch EFL writing

Abstract: This article presents a case study on the role of L1 transfer of language-specific features of information structure in very advanced L2 learners. Cross-linguistic differences in the information status of clause-initial position in a V2 language like Dutch compared to an SVO language like English are hypothesized to result in overuse of clause-initial adverbials in the writing of advanced Dutch learners of English. This hypothesis was tested by evaluating advanced Dutch EFL learners' use of clause-initial adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…While future language professionals could of course benefit from an awareness of the information-structural transfer that might occur in their L2 English (cf. Verheijen et al, 2013 andVan Vuuren, 2013), the present study has also demonstrated that the communicative effect of Dutch learners' frequent use of clause-initial place adverbials should not be overstated, since it does not seem to be immediately apparent to linguistically naïve native speakers.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…While future language professionals could of course benefit from an awareness of the information-structural transfer that might occur in their L2 English (cf. Verheijen et al, 2013 andVan Vuuren, 2013), the present study has also demonstrated that the communicative effect of Dutch learners' frequent use of clause-initial place adverbials should not be overstated, since it does not seem to be immediately apparent to linguistically naïve native speakers.…”
Section: Discussionsupporting
confidence: 48%
“…One specific instance of information-structural transfer that has been studied in much detail by Verheijen, Los and De Haan (2013), Van Vuuren (2013), and Van Vuuren and Laskin (2017) is the use of initial adverbials in L2 English by Dutch learners, which has been hypothesized to result from syntactic and pragmatic differences between the two languages. Dutch is an SOV language with V2movement in the main clause (Koster, 1975), which means that the grammatical subject can occur either pre-or post-verbally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Dutch, German has a flexible pre-verbal field since both languages have a V2 word order. This creates a Vorfeld that allows for clause-initial adverbials like locative expressions and other discourse-linking elements, such as pronominal adverbs like daaronder 'below-that' (one word in Dutch), daarmee 'there-with' , daarvoor 'there-for' , and daarop 'there-on' (Carroll et al, 2000: 453;Los & Dreschler, 2012;Van Vuuren, 2013. The entity-based perspective of English, on the other hand, is facilitated by the utterance-initial subject, because it allows for neutral existential expressions, SVO (I see/I have) and noun phrases in utterance-initial position.…”
Section: Introductionmentioning
confidence: 99%
“…There is already a lot of research on how people who speak more than one language write in their second language (e.g., Al-Ahdal and Alqasham, 2020 ; Edelsky, 1982 ; Lally, 2000 ; Lefrançois, 2001 ; Paquot, 2013 ; Uysal, 2008 ; van Weijen et al, 2009 ). Some of the characteristics that have been looked at are as follows: idea generation ( Lally, 2000 ); information structure ( van Vuuren, 2013 ); rhetorical patterns ( Uysal, 2008 ); syntactic structures ( Rankin, 2012 ) and; lexical bundles ( Paquot, 2013 ; Rankin, 2012 ). Further, Lefrançois (2001) said that in addition to knowing how to write and read, the way grammar and syntax work, how general techniques work, and how cultural schemas work in the first language could all have an effect on writing in the second language.…”
Section: Introductionmentioning
confidence: 99%